2019
DOI: 10.1158/2326-6066.cir-18-0136
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood TCR Repertoire Profiling May Facilitate Patient Stratification for Immunotherapy against Melanoma

Abstract: Many metastatic melanoma patients experience durable responses to anti-PD1 and/or anti-CTLA4; however, a significant proportion (over 50%) do not benefit from the therapies. In this study, we sought to assess pretreatment liquid biopsies for biomarkers that may correlate with response to checkpoint blockade. We measured the combinatorial diversity evenness of the T-cell receptor (TCR) repertoire (the DE 50 , with low values corresponding to more clonality and lack of TCR diversity) in pretreatment peripheral b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
109
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(116 citation statements)
references
References 60 publications
4
109
1
2
Order By: Relevance
“…Previous studies have shown TCR repertoire diversity in the peripheral blood to be an indicator of prognosis, and high TCR repertoire diversity might indicate favorable outcomes [23,27,28]. Our study supplemented the prognostic value of TCR repertoire diversity in RETdriven lung cancers but disagree with the latter notion.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Previous studies have shown TCR repertoire diversity in the peripheral blood to be an indicator of prognosis, and high TCR repertoire diversity might indicate favorable outcomes [23,27,28]. Our study supplemented the prognostic value of TCR repertoire diversity in RETdriven lung cancers but disagree with the latter notion.…”
Section: Discussioncontrasting
confidence: 55%
“…The T cell receptor (TCR) repertoire has recently emerged as a novel biomarker [23,24]. Previous pilot studies showed that tumor-infiltrated TCR clonality [25] and peripheral blood T cell receptor repertoire diversity [26][27][28] could have a potential role as predictors of the response to ICI therapy. We conducted multiplex PCR amplification on complementarity-determining region 3 (CDR3), a hypervariable region of the TCR β chain that is unique to each TC R [29] as previously described [27].…”
Section: T Cell Receptor Sequencing and Data Analysismentioning
confidence: 99%
“…The diversity of the TCR repertoire, which reflects the clonal composition of T cells may be a predictive marker of response to cancer immunotherapy 44,45 . Previous reports have shown that anti-CTLA-4 treatment leads to a significant broadening of CD8 + T-cell responses specific for melanoma and an increased diversity of T cells in blood after CTLA-4 blockade 46,47 .…”
Section: Discussionmentioning
confidence: 99%
“…The TCR clonality of both CD4 + and CD8 + T cells is more restricted than in healthy people, and broader T cell responses with greater diversity of CD4 + blood T cell clones may predict the longer survival of patients with melanoma treated with anti‐CTLA4 or PD‐1 antibodies . Many studies have shown that peripheral blood TCR diversity can be used to predict the efficacy of immunotherapy . Therefore, PEG‐rhG‐CSF may improve the efficacy of immunotherapy by increasing peripheral blood TCR diversity; however, further clinical studies are needed to confirm this.…”
Section: Discussionmentioning
confidence: 99%
“…19 Many studies have shown that peripheral blood TCR diversity can be used to predict the efficacy of immunotherapy. 17,21,33,34 Therefore, PEG-rhG-CSF may improve the efficacy of immunotherapy by increasing peripheral blood TCR diversity; however, further clinical studies are needed to confirm this. We found no MH overlap on day 3, and day 8-10 showed a significant difference between groups.…”
Section: Discussionmentioning
confidence: 99%